Fathers as sexuality educators: aspirations and realities. An Interpretative Phenomenological Analysis. Issue 1 (2nd January 2018) - Bennett, Clare; Harden, Jane; Anstey, Sally
Abstract: Men can play a significant role in teaching their children about sexuality but fathers' practices and perceptions in this domain remain under explored. This study presents an Interpretative Phenomenological Analysis of eight fathers' perceptions and practices in educating their ten-year-old children about physical maturation, reproduction and relationships. A Foucauldian analysis with a focus on governmentality and biopower revealed tensions and contradictions between the fathers' aspirations and their realities, which appeared to be underpinned by the dynamic, contradictory, shifting, plural nature of fatherhood identities. Whilst fathers wished to adhere to the cultural imperative for father–child emotional closeness, a disparity between their ambitions and their conduct emerged. Care appeared to be a deeply gendered concept for the fathers and despite their aspirations for an intimate relationship with their children, gendered norms for motherhood and fatherhood prevailed resulting in passivity in their role as sexuality educators. The study concludes by arguing that challenges to structures and subcultural contexts, which may deter fathers from fully engaging with their sons and daughters in this aspect of communication are required.